Evaluation of NADPH oxidases as drug targets in a mouse model of familial amyotrophic lateral sclerosis - Seredenina, Tamara; Nayernia, Zeynab; Sorce, Silvia; Maghzal, Ghassan J.; Filippova, Aleksandra; Ling, Shuo-Chien; Basset, Olivier; Plastre, Olivier; Daali, Youssef; Rushing, Elisabeth J.; Giordana, Maria T.; Cleveland, Don W.; et al. (Free radical biology & medicine, 2016)
Amyotrophic lateral sclerosis (ALS) is an incurable neurodegenerative disease characterized by progressive loss of motor neurons, gliosis, neuroinflammation and oxidative stress. The aim of this study was to evaluate the involvement of NADPH oxidases (NOX) in the oxidative damage and progression of ALS neuropathology. We examined the pattern of NOX expression in spinal cords of patients and mouse models of ALS and analyzed the impact of genetic deletion of the NOX1 and 2 isoforms as well as pharmacological NOX inhibition in the SOD1G93A ALS mouse model. A substantial (10–60 times) increase of NOX2 expression was detected in three etiologically different ALS mouse models while up-regulation of some other NOX isoforms was model-specific. In human spinal cord samples, high NOX2 expression was detected in microglia. In contrast to previous publications, survival of SOD1G93A mice was not modified upon breeding with constitutive NOX1 and NOX2 deficient mice. As genetic deficiency of a single NOX isoform is not necessarily predictive of a pharmacological intervention, we treated SOD1G93A mice with broad-spectrum NOX inhibitors perphenazine and thioridazine. Both compounds reached in vivo CNS concentrations compatible with NOX inhibition and thioridazine significantly decreased superoxide levels in the spinal cord of SOD1G93A mice in vivo. Yet, neither perphenazine nor thioridazine prolonged survival. Thioridazine, but not perphenazine, dampened the increase of microglia markers in SOD1G93A mice. Thioridazine induced an immediate and temporary enhancement of motor performance (rotarod) but its precise mode of action needs further investigation. Additional studies using specific NOX inhibitors will provide further evidence on the relevance of NOX as drug targets for ALS and other neurodegenerative disorders. •NOX2 is expressed in microglia; its expression is increased during ALS progression.•LC/MS/MS of hydroethidine show increased level of O2∙− in mouse ALS spinal cord.•Genetic deletion of NOX1 or NOX2 does not prolong the survival of SOD1G93A mice.•N-substituted phenothiazines do not prolong the survival of SOD1G93A mice.•Thioridazine decreases O2∙− level and microglial markers in mouse ALS spinal cord.